2021
DOI: 10.3390/v13091787
|View full text |Cite
|
Sign up to set email alerts
|

De-Escalating Strategies in HPV-Associated Head and Neck Squamous Cell Carcinoma

Abstract: HPV-related head and neck squamous cell carcinoma (HNSCC) has emerged as a diverse clinical and biological disease entity, mainly in young patients with oropharyngeal tumors who are nonsmokers and nondrinkers. Indeed, during the past few years, the pendulum has shifted towards a new epidemiological reality, the “HPV pandemic”, where the majority of oropharyngeal squamous cell carcinomas (OPSCCs) are attributed to HPV. The oncogenic potential of the virus is associated to its capacity of integrating oncogenes E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Although de-escalation of chemoradiotherapy has been discussed for patients with HPV-associated OPSCC, 35 our results suggest that the therapeutic strategy should be carefully designed depending on the tumor stage. Since the HPV infection rate was <1% in the pure HP/LSCC group, the prognostic significance of HPV infection in these patients is still unclear.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although de-escalation of chemoradiotherapy has been discussed for patients with HPV-associated OPSCC, 35 our results suggest that the therapeutic strategy should be carefully designed depending on the tumor stage. Since the HPV infection rate was <1% in the pure HP/LSCC group, the prognostic significance of HPV infection in these patients is still unclear.…”
Section: Discussionmentioning
confidence: 87%
“…We performed ISH to detect HPV RNA using an E6/E7 mRNA probe set (Advanced Cell Diagnostics) for 18 types of HR-HPV (types 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 73, and 82) with an RNA scope 2.5HD detection kit (Advanced Cell Diagnostics) according to the manufacturer's protocol. Any nuclear or cytoplasmic dots were considered positive.…”
Section: Hpv In Situ Hybridizationmentioning
confidence: 99%
“…65 Several studies are ongoing in HPV+ OPC to evaluate different strategies to reduce toxicities while maintaining the high survival rate in this subpopulation of head and neck patients with cancer. 66 The treatment opportunities may be summarized as the use of surgery as the first option to reduce post-operative treatment, the modulation of systemic therapies concurrently to radiation, and the reduction of dose or volume of radiation. Surgical resection and deintensified RT in these patients continues to be an experimental approach, and larger randomized studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the trials of CRT included in the current analysis, only five reported outcomes of interest in patients with p16-positive OPSCC, precluding conclusive results for the exploratory analysis in that subpopulation. Future research can potentially focus on evidence bases other than the one synthesized in the current study; for example, the OS-EFS correlation could be further explored in trials evaluating RT alone in p16-positive patients, particularly those using the de-escalation treatment strategy with lower toxicity rates ( 74 ). Such trials, however, were not directly related to the research questions of the current analysis and were not included in our SLR.…”
Section: Discussionmentioning
confidence: 99%